Analysis of spatial heat and mass transfer in the channels of a forming tool during polymer coextrusion - Kozitsyna, Mariya Vladimirovna; Trufanova, Nataliya Mikhaylovna (Computational Continuum Mechanics, 2018)
At present, there is a growing demand for use of crosslinked polyethylene (PE) as an insulating material possessing high operating temperature. One way to obtain multi-layer insulation of cables from cross-linked PE is coextrusion of grafted PE with its further cross-linking in steam boilers. The shapes of conical-cylindrical configuration channels, found by the authors in the literature, are significantly different from the actual cable head. In this article, the formulation and numerical realization of the spatial problem of heat and mass transfer of nonlinear plastics in the channels of a coextrusion cable head of complicated geometry are present. It is important to study and analyze the flows of melts of materials with different properties, because a three-layer coating is created in the forming tool. Largely the flow process is determined by the nonlinear character of the dependence of the melt viscosity on temperature and on the strain rate tensor. For polymer isolation, the cross-linked PE was used. Determination of the rheological parameters of this polymer using a laboratory rheometer is very difficult due to the process of cross-linking. In the paper, three geometric models of a forming tool, each of which differs from the previous shape and length of the channels, are considered. The models were realized using the finite element method in ANSYS software package. Maximum and average temperature and pressure dependences are presented for each geometric channel. Analysis of the results has revealed that the geometric model closest to the actual cable head better describes the processes of heat and mass transfer compared to other models.